On the Impact of Contact Selectivity and Charge Transport on the Open‐Circuit Voltage of Organic Solar Cells. Issue 5 (9th November 2016) - Spies, Annika; List, Mathias; Sarkar, Tanmoy; Würfel, Uli
Abstract : The selectivity of electrodes of solar cells is a critical factor that can limit the overall efficiency. If the selectivity of an electrode is not sufficient both electrons and holes recombine at its surface. In materials with poor transport properties such as in organic solar cells, these surface recombination currents are accompanied by large gradients of the quasi‐Fermi energies as the driving force. Experimental results from current–voltage characteristics, advanced photo‐ and electroluminescence as well as charge extraction of three different photoactive materials are shown and compared to drift‐diffusion simulations. It can be concluded that in cases of electrodes with reduced selectivity the decrease of the open‐circuit voltage can be divided into two distinct contributions, the reduction of the overall steady‐state charge carrier density and the gradients of the quasi‐Fermi energies. The results clearly show that for photoactive layers with poor transport properties, the gradient of the quasi‐Fermi energy in the vicinity of the contact is the main contribution to the loss in open‐circuit voltage. For imbalanced mobilities, this gives rise to the phenomenon that it is more challenging to realize a selective contact for the less mobile charge carrier, i.e., the hole contact in most organic solar cells. Abstract : The impact of charge carrier mobility and electrode selectivity on surface recombination is investigated by drift‐diffusion modeling, charge extraction, electro‐ and photoluminescence. It is shown that for organic solar cells the reduced open‐circuit voltage is not only due to actual recombination of charge carriers at the contact but mainly a consequence of the required driving force for the majority carriers.